Level of Cadmium and Lead Contamination in Some Urban Soils and Vegetables of Bangladesh - Farzana Ahmed Rumi; Md. Shoffikul Islam; Mukhlesur Rahman Mukit; Md. Abul Kashem (Journal of the Indian Society of Soil Science, 2024)
Consuming vegetables produced in toxic metal-contaminated soil is hazardous to one’s health. In this study, 66 samples of leafy vegetables and 66 samples of rhizosphere topsoil were collected from three contaminated locations in Chattogram, Bangladesh, to investigate the level of contamination, accumulation, and the impact of cadmium (Cd) and lead (Pb). The mean values were 0.79 mg kg-1 for Cd and 52.85 mg kg-1 for Pb in soils. Results revealed that 100% of the samples from Nasirabad, and 78% of the samples from Halishahar, and 13% of the sample from Jamburi Park had Cd concentrations above threshold value of Cd in natural agricultural soil in China (0.6 mg kg-1) while 100% of the samples collected from three sites had Pb concentrations below the threshold value of Pb in natural agricultural soil in China (350 mg kg-1). The Cd and Pb levels in the vegetable samples were 3.17 and 41.39 mg kg-1, respectively. The mean bioconcentration factor (BCF) values for Cd ranged from 1.85 to 11.89, while those for Pb ranged from 0.43 to 1.23. Water spinach had the highest BCF among the five-vegetable species, whereas sweet gourd had the lowest. The extractability of Cd and Pb in soils of three contaminated sites were determined by single extraction 1MHCl and DTPA methods. Between the extractants, 1 M HCl extracted the largest portion of Cd (55 to 94%) and Pb (60 to 94%) from soils than DTPA extractants. The extractable Cd and Pb with DTPA were 44% and 22%, but with 1 M HCl, they were 76 and 79% in soils of the three contaminated area, respectively. The concentrations of Cd and Pb in the vegetable species had a strong positive relationship (p<0.001) with the total, DTPA, and 1M HCl-extraction of Cd and Pb in rhizosphere topsoil. In conclusion, the long-term consumption of Cd and Pb-contaminated vegetables may put the local population at risk.